Establishing a mesenchymal stem cell bank from umbilical cord tissue for cell therapy and initial application in the treatment of knee osteoarthritis at Tam Anh general hospital - Long, Nguyen Tam; Viet, Trinh Tuan; Bich, Nguyen Thi; Duong, Tran Thuy; Huong, Nguyen Xuan; Binh, Trinh Xuan; Thanh, Tran Thi Hoai; Nga, Tham Thi Thu; Nam, Nguyen Trung (Vietnam Journal of Biotechnology, 2024)
Osteoarthritis (OA) is a natural aging process of joints that often occurs as age increases. In knee osteoarthritis, the cartilage that cushions the ends of the thigh bone and shinbone within the knee joint deteriorates, leading to a loss of cushioning and flexibility. This can result in pain, swelling, and stiffness when moving the knee joint. In the treatment of knee osteoarthritis, methods often include symptom management with pain-relieving and anti-inflammatory medications, lifestyle modifications to reduce stress on the knee joint; in some cases, surgery may be considered if nonsurgical interventions are ineffective. Stem cell therapy has emerged as a promising approach for treating knee osteoarthritis. This method has been demonstrated to be safe and effective. Still, one of the most important considerations when using stem cell therapy is quality regulation and safety standards regarding cell culture. This has led to the emergence of stem cell banks, where they are manufactured, preserved and stored. In this study, we utilized stem cells derived from allogeneic umbilical cord tissue. The stem cells were expanded and administered to patients via two injections spaced one month apart, with follow-up lasting an additional six months. The initial treatment results using stem cells for patients with knee osteoarthritis have been very promising. Through assessments of mobility, pain levels (measured by the VAS), and improvement in quality of life (measured by the Lequesne index) over 6 months, the research team has demonstrated the effectiveness of using mesenchymal stem cells (MSCs) from umbilical cord tissue for treating knee osteoarthritis.